Bahasa Inggris - Girsang, Martina; Manalu, Mega Patrisia; Cecilia, Prity; Agnes, Rainy Agria; Sinambela, Rifkha (BASIS (Bahasa dan Sastra Inggris), 2023)
This study analyses the non-normative feminism performed by the characters in a play entitled No Exit by Jean Paul Sartre. The concept of feminism is linked to the liberation of women from the control and dominance of men. On the other hand, non-stereotypical principles are the development of individuals. In this non-normative discussion, the author relates it to the realm of feminism and lesbianism which is part of radical feminist theory. The objective of the study is to identify the tendency of non-normative of the characters named Inès, and Estelle in the play. This study is a literary criticism using qualitative descriptive method. The results of the study showed that the two main female characters show non-normative feminism attitudes, including having a sexual orientation that slightly deviate from French society at that time, not wanting to be in a relationship with men, and also not wanting to give birth and become a mother. As the title No Exit reminds us, Inès and Estelle exhibit their true identities only in a world closed to the rest of society; even in this space they are always reprimanded. Thus, Sartre criticizes the lack of options for non-stereotypical women in French society, as well as the tendency to view these women as inherently ‘immoral’.